Assessing Knowledge and Awareness in Intercultural Communicative Competence Among EFL Postgraduate Learners: A Situational Approach - Osama Aljamaly; Asst. Prof. Dr. Omar Ali Ilyas (مجلة النور للدراسات الانسانية)
The study at hand attempts to assess intercultural communicative competence (ICC) level for postgraduate English Foreign Language learners (EFLs) in three Iraqi’s universities, using triangulation methodology in collecting data to fill in the gap of using inaccurate methodologies in assessing ICC.The study adopted a modified model of Alvino Fantini's (2001) model of intercultural communicative competence. This study will concentrate on two components of ICC: awareness and knowledge. The tools used in this study are intercultural communicative competence questionnaire (ICCQ) which explores how students perceive their intercultural competence (IC), oral proficiency interview (OPI) to test learners’ oral language proficiency, and situational judgment test (SJT) to objectively assess their ICC level. Therefore, the study belongs to mix-method methodology. The sample were thirty postgraduate EFL learners, with 10 individuals from the University of Mosul, 10 from the University of Anbar, and 10 from the Tikrit University and each group of ten is homogeneous in terms of gender. The collected data underwent several statistical analyses to obtain reliable results. The results reveal that the ICC level among postgraduate EFL learners in the three universities is generally low.